TNCs arbete med Eurodicautom, Europeiska kommissionens termdatabas - Brewitz, Erica; Bucher, Anna-Lena (Nordiske Studier i Leksikografi, 2001)
The paper gives a brief orientation of the goals and activities of The Swedish Centre for Technical Terminology (TNC) and the reasons why subject field specialists feel the need of determining and describing subject field related concepts and terms. The principles and methods of terminology work are described, and the importance of having subject field specialists participating in the work is particularly emphasized. Since Sweden's membership in the EU in 1995, TNC's activities have been dominated to a !arge extent by the comprehensive task from the European Commission of updating the terminologic database Eurodicautom with Swedish terminology in various fields. In four different projects, each running for twelve months, TNC has been supplementing approximately 140 000 term records with Swedish terms and references, and to some extent also with definitions and comments. The working principles in some respects diverge from the traditional methods of terminology work. In other respects, e.g. the close cooperation with subject field specialists, it has been possible to retain the principles. However, TNC has had to adapt some of the working methods to the specific conditions of these projects. The last part of the paper is a report from one of the specialists, a biologist. She decribes her motives for applying for a job within this project, and her experiences after having been involved in the work for more than a year.